2013
DOI: 10.1071/mf12128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient loading on the trophic state of Lake Brunner

Abstract: Abstract. Lake Brunner, an oligotrophic monomictic lake on the West Coast of the South Island of New Zealand, is under pressure from urban expansion and increased farming activity, which has led to concern for the effects on water quality in the lake. Epilimnetic nitrogen, phosphorus and chlorophyll a concentrations have increased since 1992, and Secchi depth decreased. This suggests an increased algal productivity caused by increased nutrient inputs, further supported by increased hypolimnetic oxygen depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Productivity in Lake Brunner is limited by the availability of P as demonstrated by very low concentrations of inorganic P relative to inorganic N. The DIN-to-FRP mass ratio in the epilimnion is 131 (Verburg et al 2013). Lake Brunner is vulnerable to changes in P loading because of the large difference between the N and P concentrations relative to the stoichiometric demand of phytoplankton productivity.…”
Section: Dairy Farming and Lake Brunnermentioning
confidence: 99%
See 2 more Smart Citations
“…Productivity in Lake Brunner is limited by the availability of P as demonstrated by very low concentrations of inorganic P relative to inorganic N. The DIN-to-FRP mass ratio in the epilimnion is 131 (Verburg et al 2013). Lake Brunner is vulnerable to changes in P loading because of the large difference between the N and P concentrations relative to the stoichiometric demand of phytoplankton productivity.…”
Section: Dairy Farming and Lake Brunnermentioning
confidence: 99%
“…Annual rainfall in the Lake Brunner catchment is highly variable, ranging from 3 m year À1 at the northern end of the lake to 4.8 (maximum 6.8) m year À1 at Inchbonnie, 10 km away at the southern end of the lake. Lake Brunner is oligotrophic (total phosphorus (TP) ,10 mg m À3 ) but Secchi depth transparency has decreased since the early 1990s from ,6.5 to 5.5 m (Verburg et al 2013). The decrease in transparency corresponds to an observed increase in chlorophyll a, an algal pigment that is a good proxy for algal abundance in the lake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Wilcock et al (2013b) examined catchment sources and pathways for water-quality contaminants. The study by Verburg et al (2013) assessed the relative of these contaminants on an oligotrophic lake (Brunner). Wilcock et al (2013b) found that while trends were decreasing (i.e.…”
Section: Linking Nutrient Losses To Effects and Management Across Scalesmentioning
confidence: 99%
“…Moreover, at the farm scale the measured loads closely matched modelled loads, indicating that attenuation in the stream network was limited and that mitigation should be directed mostly at the source. Verburg et al (2013) then went onto assess the relative impact of the loads of N and P, finding that the Vollenweider model predicted a mean P concentration close to the observed concentration and that algal productivity was most strongly stimulated by additional inputs of P to the lake. They indicated using the Vollenweider model that at the present rate of increasing agricultural intensification and P loading from the catchment, Lake Brunner would likely change from oligotrophic to mesotrophic.…”
Section: Linking Nutrient Losses To Effects and Management Across Scalesmentioning
confidence: 99%